2007
DOI: 10.1038/sj.bmt.1705856
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for fatal infectious complications developing late after allogeneic stem cell transplantation

Abstract: Infectious complications remain a major problem contributing to significant mortality after hematopoietic allogeneic stem cell transplantation (HSCT). Few studies have previously analyzed mortality due to late infections. Forty-four patients dying from an infectious complication were identified from a cohort of 688 consecutive patients surviving more than 6 months without relapse. A control group of 162 patients was selected using the year of HSCT as the matching criterion. Out of 44 patients, 30 (68%) died fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 53 publications
4
65
1
1
Order By: Relevance
“…The Bone Marrow Transplantation Registry has reported that fatal infections are a prevalent cause of late mortality, with risk factors for infectious death including acute GVHD, chronic GVHD, CMV infection, mismatched or unrelated donor and TBI. 5,13 Chronic GVHD has been identified as the primary isolated risk factor for late infections after HSCT in adult patients. 14 These infections have been attributed to functional asplenia, 14 impaired T and B cell reconstitution and the immunosuppressive therapy used to treat chronic GVHD.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bone Marrow Transplantation Registry has reported that fatal infections are a prevalent cause of late mortality, with risk factors for infectious death including acute GVHD, chronic GVHD, CMV infection, mismatched or unrelated donor and TBI. 5,13 Chronic GVHD has been identified as the primary isolated risk factor for late infections after HSCT in adult patients. 14 These infections have been attributed to functional asplenia, 14 impaired T and B cell reconstitution and the immunosuppressive therapy used to treat chronic GVHD.…”
Section: Study Populationmentioning
confidence: 99%
“…2 In survivors of allogeneic HSCT, relapse of the primary disease and chronic GVHD are the most frequent causes of late mortality in adults. 3,5 Relapsed disease and second malignancies are the main causes of late mortality after autologous HSCT. 6,7 However, as the distribution of cancers, for which HSCT is indicated differs between adults and children, 4 the contribution of relapse to late mortality in children may not mirror that seen in adult cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the therapies preventing and treating graft-versus-host-disease (GVHD) and cytopenia, HSCT recipients have a high risk of acquiring invasive fungal infection (IFI) (Jantunen et al, 1997;Bjorklund et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Infectious complications represent an important cause of non-relapse morbidity and mortality even more than ten years after allogeneic stem cell transplantation. 26,27 Extensive chronic graft-versus-host disease (GVHD), cytomegalovirus (CMV) status, unrelated donor transplantation, irradiation in conditioning regimen and age have been established as important risk factors for late infections, [28][29][30] but there are no objective parameters to define a dysfunction of the immune system in long-term survivors. Therefore, we investigated the association between serum MBL levels and the occurrence of severe infections during different periods after transplantation in a single center cross-sectional study of a unique cohort of very long-term survivors.…”
Section: Introductionmentioning
confidence: 99%